Endogenous Retrovirus 3 – History, Physiology, and Pathology - Bustamante Rivera, Yomara Y.; Brütting, Christine; Schmidt, Caroline; Volkmer, Ines; Staege, Martin S. (Frontiers in Microbiology, 2018)
Endogenous viral elements (EVE) seem to be present in all eukaryotic genomes. The composition of EVE varies between different species. The endogenous retrovirus 3 (ERV3) is one of these elements that is present only in humans and other Catarrhini. Conservation of ERV3 in most of the investigated Catarrhini and the expression pattern in normal tissues suggest a putative physiological role of ERV3. On the other hand, ERV3 has been implicated in the pathogenesis of auto-immunity and cancer. In the present review we summarize knowledge about this interesting EVE. We propose the model that expression of ERV3 (and probably other EVE loci) under pathological conditions might be part of a metazoan SOS response.